Improving Halal Traceability Process in the Poultry Industry Utilizing Blockchain Technology: Use Case in Indonesia - Sidarto, Larissa P.; Hamka, Aditya (Frontiers in Blockchain, 2021)
Demand for Halal food has significantly increased with the growing Muslim population and society’s interest in sustainable food production. However, there has been an increase in concerns regarding the Halal food labeling transparency process, with misleading labels found across the world. Blockchain-based traceability systems are a potential solution for current limitations in monitoring the food’s production process due to its inherent decentralization and immutable nature. The technology allows stakeholders, including consumers, to promote farm to fork transparency, where traceability is a core component. This paper will explore the blockchain-based traceability system use case implemented by Indonesian poultry player PT Sreeya Sewu Indonesia Tbk. Utilizing a blockchain-based system as a foundation for traceability shows promising results: data throughout the process is recorded permanently, and difficult to tamper. Although the system does not eliminate the possibility of incorrect information being recorded, the same immutability characteristics will keep the new knowledge of fraud permanent if found out during the audit. This layer of accountability contributes to the transparency that benefits both the consumers and stakeholders of the value chain.